Academic freedom in Africa : the struggle rages on - Ndasauka, Yamikani; Sandifolo Kamchedzera, Garton (New York : Routledge, 2025)
"This book leaves no stone unturned in its comprehensive examination of the complex challenges surrounding academic freedom in Africa. Drawing on diverse perspectives and methodologies, it delves into the historical, philosophical, legal, and socio-political dimensions shaping academic freedom across the continent. The authors grapple with colonial legacies, tensions between Western and African notions of intellectual liberty, government authoritarianism, and institutional constraints that hinder open discourse and the pursuit of knowledge. The book highlights systemic obstacles and promising avenues for progress through case studies, comparative analysis, and empirical research, such as constitutional reforms, scholar activism, and regional networks. This thought-provoking volume offers critical insights into the state of academic freedom in Africa, emphasising the necessity of supporting African voices and agencies in the quest for meaningful intellectual autonomy. Academic Freedom in Africa is an essential read for students, scholars, policymakers, and anyone concerned with the future of higher education and democracy on the continent"--
Chapter 1. The quest for academic freedom in Africa / Yamikani Ndasauka -- Part 1. State actors, democracy and academic freedom -- Chapter 2. Navigating between liberal and communitarian perspectives of academic freedom in Africa / Simon Makwinja, Grivas Kayange and Lawrence Mpekansambo -- Chapter 3. Academic freedom and democracy in Africa / Hajer Kratou and Liisa Laakso -- Chapter 4. Geopolitics and the challenge of academic freedom in Africa / Uchenna Azubuike Ezeogu and Chinweuba, Gregory Emeka -- Chapter 5. Theme-Rheme analysis and ideological representations in Malawian and Zambian online news reporting of academic freedom sagas / Mtende Wezi Nthara -- Chapter 6. Questioning academic freedom invocation in the Glenda Gray controversy / Seán M. Muller -- Part 2. Education reforms vis-a-vis academic freedom -- Chapter 7. The tensions, contradictions, and paradoxes of 'Entrepreneurial University' -- Reforms and academic freedom / Happy Mickson Kayuni -- Chapter 8. Problematising academic freedom in Nigerian universities / Lucky O. Akaruese -- Chapter 9. African Indigenous pedagogies as a key driver for academic freedom / Patrick Juma and Jerry Rutsateb -- Chapter 10. Conviviality in journalism studies and academic freedom / Mwaona Nyirongo -- Chapter 11. Professionalism and the discourse of academic freedom in higher education institutions: Evidence from Malawi and Japan / Foster Gondwe and Masayasu Sakaguchi -- Chapter 12. A dilemma regarding academic freedom and public accountability in higher education / Thaddeus Metz -- Part 3. Reflections on Malawi's 2011 academic freedom movement -- Chapter 13. Police handling of academic freedom impasse and students with disabilities in Malawi / Elizabeth T. Kamchedzera -- Chapter 14: The academic freedom struggle as a test of employee commitment at the University of Malawi / Tiyesere Mercy Chikapa- Jamali -- Chapter 15. Metaphorisation of color red during the academic freedom saga in Malawi / Timwa Lipenga -- Chapter 16. Rhetorical analysis of slogans in the struggle for academic freedom in Malawi / Anthony Mavuto Gunde -- Chapter 17. Battle lines in Africa's struggle on academic freedom / Garton Kamchedzera.
Keywords: Academic freedom -- Africa; Higher education and state -- Africa; Intellectuals -- Africa; Intellectuals -- Political activity -- Africa; Africa -- Intellectual life; EDUCATION / Philosophy & Social Aspects; PHILOSOPHY / Epistemology